Detection of the BRAF V600E mutation in serous ovarian tumors: a comparative analysis of immunohistochemistry with a mutation-specific monoclonal antibody and allele-specific PCR - Bösmüller, Hans; Fischer, Anna; Pham, Deborah L.; Fehm, Tanja; Capper, David; Deimling, Andreas von; Bonzheim, Irina; Staebler, Annette; Fend, Falko (Human pathology, 2013)
Mutations of components of the mitogen-activated protein kinase pathway, mainly BRAF, are common in serous ovarian borderline tumors, whereas high-grade serous ovarian carcinomas rarely show this feature. With the advent of specific kinase inhibitors active against BRAF-mutated cancers, rapid and sensitive detection of the BRAF V600E, by far the most common mutation of this gene, is of great practical relevance. Currently, BRAF mutations are detected by DNA-based techniques. Recently, a monoclonal antibody (VE1) specific for the BRAF V600E protein suitable for archival tissues has been described. In this study, we compared detection of the V600E mutation in serous ovarian tumors by VE1 immunostaining and by allele-specific polymerase chain reaction. All 141 cases of high-grade serous ovarian cancer showed negative or rarely weak, diffuse background VE1 immunostaining, and BRAF wild type was confirmed by molecular analysis in all tested cases. In contrast, 1 (14%) of 7 low-grade serous carcinomas and 22 (71%) of 31 serous borderline tumors revealed moderate to strong VE1 positivity. Immunostaining was clearly evaluable in all cases with sufficient tumor cells, and only rare cases with narrow cytoplasm were difficult to interpret. The V600E mutation was confirmed by allele-specific polymerase chain reaction and sequencing in all VE1-positive cases. Two VE1-positive cases with low epithelial cell content required repeat microdissection to confirm the presence of the mutation. Immunohistochemistry with the VE1 antibody is a specific and sensitive tool for detection of the BRAF V600E mutation in serous ovarian tumors and may provide a practical screening test, especially in tumor samples with low epithelial content.